Modeling a Fluidized Bed Dryer Through Computational Fluid Dynamics and the Discrete Element Method - Muñoz-Lagos, A; Hurtado-Cruz, J; Vargas-Norambuena, J; Jara-Munoz, P; Jarufe-Troncoso, J; Perez-Cortes, S (John Wiley and Sons Inc, 2021)
The internal phenomena of a concentrate dryer were studied to significantly improve the modeling and design of a melting process. The present study coupled computational fluid dynamics and the differentiated elements method to obtain detailed information about complex phenomena in the simulated obtention of copper metal while keeping fluids physically stable. It was possible to understand the behavior from the point of view of the fluid and dynamics with acceptable margins of error. The study is part of the critical process line at Caletones Smelter in Chile, which produces ca. 450 000 tons of fine copper per annum, representing 2 % of total annual global copper demand and making the subject of this study highly relevant. © 2021 Wiley-VCH GmbH